A desconsideração da personalidade jurídica na execução civil segundo o devido processo legal - Prudente, Gabriel Ribeiro (2014)
This paper deals with the theory of disregard of legal entity when applied by judges in civil enforcement proceedings. Firstly, we seek to present the introductory lessons on the theory of disregard, describing its appearance and the way they have developed and fixed their theoretical fundaments for, then, enter specifically on issues related to the implications of the civil enforcement proceedings. From this point, you can see that the figure of ownership unbundling, resulting from the legal status granted to companies, is not an absolute right. The jurisprudence of common law countries mitigated this institute through the creation of the theory of disregard of legal entity, a technique that allows to be pierced the "veil" protector of the companies to directly reach the assets of the shareholders for debts incurred on behalf of the legal person. However, the application of this modern tool in the civil enforcement proceeding - very frequent activity in the current Brazilian forensic practice - requires compliance with certain requirements, the presence of some assumptions and observance of certain forms, without occurs an abuse in its application and, consequently, some vulgarization of the institute. The fact that the doctrinal and jurisprudential about certain aspects of the application of the disregard of legal entity in the execution civil procedure are far from a consensus, as well as the upcoming regulation of the institute in the new procedure civil code, are the reasons that motivated this study, which will be dedicated to analyzing some of the main controversial points